2019
DOI: 10.1113/ep087783
|View full text |Cite
|
Sign up to set email alerts
|

μ‐Opioid receptor signalling via PI3K/Akt pathway ameliorates lipopolysaccharide‐induced acute respiratory distress syndrome

Abstract: New Findings What is the central question of this study?The aim was to investigate the role of μ‐opioid receptors in acute respiratory distress syndrome and whether their protective effect is mediated via the PI3K/Akt signalling pathway. What is the main finding and its importance?Our findings show that activation of μ‐opioid receptors ameliorates lung injury, and the effects are reversed by the PI3K inhibitor, wortmannin. Abstract The main pathology of acute respiratory distress syndrome (ARDS) is the accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The study by Ji and Wang () complements and extends previous work revealing that μ‐opioid activation is effective in attenuating lung injury in rats via downregulation of the pro‐inflammatory transcription factor nuclear factor‐κB (Zhang, Du, Zhou, Wang, & Li, ), a downstream target of the PI3K/Akt signalling cascade. Together, these studies provide a mechanistic link supporting anti‐inflammatory actions of μ‐opioid receptor activation relevant to pulmonary disease, albeit that specific cell types were not characterized in the study by Ji and Wang ().…”
supporting
confidence: 68%
See 2 more Smart Citations
“…The study by Ji and Wang () complements and extends previous work revealing that μ‐opioid activation is effective in attenuating lung injury in rats via downregulation of the pro‐inflammatory transcription factor nuclear factor‐κB (Zhang, Du, Zhou, Wang, & Li, ), a downstream target of the PI3K/Akt signalling cascade. Together, these studies provide a mechanistic link supporting anti‐inflammatory actions of μ‐opioid receptor activation relevant to pulmonary disease, albeit that specific cell types were not characterized in the study by Ji and Wang ().…”
supporting
confidence: 68%
“…In this issue of Experimental Physiology , Ji and Wang () provide evidence that μ‐opioid receptor activation ameliorates pathophysiological features in an animal model of ARDS. Tracheal instillation of lipopolysaccharide in adult mice evoked pulmonary injury characterized histologically and by evidence of pulmonary oedema and increased protein concentration in the bronchoalveolar lavage fluid, with augmented levels of inflammatory mediators (interleukin‐1β and tumour necrosis factor‐α) and increased myeloperoxidase activity, a surrogate marker of neutrophil infiltration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, AKT is generally recognized as a key factor in PI3K (phosphatidylinositol 3-kinase) /AKT pathway and acts as a crucial role in cell differentiation, proliferation, metabolism, apoptosis, protein synthesis and transcription (Li et al 2015). Previous studies have indicated that ARDS can be treated by the inhibition of PI3K/AKT signaling pathway (Ji and Wang 2019;Li et al 2018b;Yanagi et al 2015;Zheng et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AKT is generally recognized as a key factor in PI3K (phosphatidylinositol 3-kinase) /AKT pathway and acts as a crucial role in cell differentiation, proliferation, metabolism, apoptosis, protein synthesis and transcription [11]. Previous studies have indicated that ARDS can be treated by the inhibition of PI3K/AKT signaling pathway [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%